Peran Knowledge Sharing Dalam Meningkatkan Innovative Work Behaviour Pada Pelaku UMKM Melalui Mediasi Work Flezibility Di Kabupaten Buton Selatan - Efrendi, Riski; Suwarto, Suwarto; Astaginy, Niar (University of Riau Kepulauan, 2025)
This research seeks to identify the influence of knowledge sharing regarding innovative work behavior via work flexibility mediation. This research employs a quantitative method approach. The process of gathering data in this research uses observation, questionnaires and documentation. The study's population is all msmes in south buton regency. Meanwhile, this study's sample comprised 378 MSMEs. Testing of the research instrument used validation tests and reliability tests with spss 25.0. The data analysis technique employed in this study includes the measurement model test and structural model test. Based on the results of the study it is known that: (1) knowledge sharing has a positive and significant effect on work flexibility. (2) work flexibility has no effect on innovative work behavior. (3) knowledge sharing has a positive and significant effect on innovative work behavior. (4) knowledge sharing through work flexibility has no effect on innovative work behavior.